LE DEVELOPPEMENT DE L’HEVEACULTURE LES MUTATIONS AGRICOLES ET SPATIO-FONCIERES A SONGON - Paul Eric, Kouame Dhédé (European Scientific Journal, ESJ, 2014)
The present article approaches the question of the expansion of the rubber cultivation in one pioneer area in Côte d’Ivoire. This culture introduced since the colonial period in the sub-prefecture of Songon transformed the landscape that was previously an important land reserve. She also transformed the local agricultural economy and unstructured customary tenure and generated at the autochthonous populations a new rapport with the earth.